The story of folk music - Berger, Melvin (New York : S. G. Phillips, 1976)
Examines the evolution of American folk music due to the influences of politics, different personalities, and musical instruments.
Includes indexes
Bibliogr.: p. 119-122.
Keywords: Folk music -- History and criticism; Folk music